Penerapan Prinsip Bioetik dalam Pengujian Escherichia coli pada Air dan Salmonella pada Ikan Nila (Oreochromis niloticus) Menggunakan Media Compact Dry Berdasarkan Standar ISO/IEC 17025 di Laboratorium BPPMHKP Medan I - Andina Ayu Syahputri; Dini Dara Arifia; Nurbaity Situmorang; Mhd Yusuf Nasution; Widya Arwita (Jurnal Biogenerasi, 2026)
Food safety and environmental quality are critical aspects in maintaining public health, particularly in fishery products and water sources that are vulnerable to contamination by pathogenic microorganisms. This study aims to identify the presence of Escherichia coli in water samples and Salmonella in tilapia (Oreochromis niloticus), as well as to analyze the use of Compact Dry media based on ISO/IEC 17025 and the implementation of bioethical principles in microbiological testing. This research employed a descriptive laboratory approach conducted at the BPPMHKP Medan I Laboratory using Compact Dry media based on AOAC methods. The samples consisted of lake water and tilapia, which were tested through enrichment, inoculation, incubation, and colony observation stages. The results showed no growth of Escherichia coli colonies on Compact Dry EC media and no Salmonella colonies on Compact Dry SL media, indicating that all samples were negative for the tested bacteria. The use of Compact Dry media in this study complied with ISO/IEC 17025 standards, as indicated by systematic procedures, the use of validated media, and laboratory quality control. Furthermore, bioethical principles, including scientific integrity, responsibility, biosafety, and accountability, were applied throughout all stages of testing. Therefore, this study demonstrates that the use of validated media and the application of bioethical principles play an important role in ensuring valid, reliable, and accountable laboratory results.